2014
DOI: 10.1007/s10853-014-8697-y
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of aluminum sludge (AS) to enhance mine tailings-based geopolymer

Abstract: This paper investigates the feasibility of using aluminum sludge (AS) to enhance copper mine tailings (MT)-based geopolymer. The Si/Al and Na/Al molar ratios were adjusted by adding AS into the high silica content MT and using different amounts of NaOH. Unconfined compression tests and SEM, XRD, and FTIR studies were conducted on geopolymer specimens prepared at different Si/Al and Na/Al ratios and after 7-day curing. The results indicate that by adding AS and utilizing appropriate amount of NaOH, the unconfin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 36 publications
5
18
0
Order By: Relevance
“…For all specimens, the average 14 day UCS and 28 day UCS are only 8.8% and 14% higher than the average 7 day UCS, respectively. This means a major portion of the ultimate strength of geopolymer mortar is gained within the first 7 days, which confirms the findings from [27,[32][33][34][35][36]. Fig.…”
Section: Thermal Testsupporting
confidence: 86%
“…For all specimens, the average 14 day UCS and 28 day UCS are only 8.8% and 14% higher than the average 7 day UCS, respectively. This means a major portion of the ultimate strength of geopolymer mortar is gained within the first 7 days, which confirms the findings from [27,[32][33][34][35][36]. Fig.…”
Section: Thermal Testsupporting
confidence: 86%
“…The reduction in the intensity of the quartz peak was also evidence of the participation of quartz in the dissolution reactions. This phenomenon of the dissolution of crystalline species has also been reported in literature [24]. GP0 and GPS1 showed the formation Calcium Silicate Hydrate (CSH) around 20°and 78° [28,29].…”
Section: Spectroscopic Analysissupporting
confidence: 81%
“…This was due to that the aluminate activation resulted in the formation of calcium silicate hydrate and calcium aluminate silicate hydrate in the geopolymers whereas silicate activation resulted in the formation of calcium silicate hydrate only. It has been shown that the right balance between Si and Al in the precursors or activating materials is important to get a high UCS [24]. This is because the two have to dissolve and then rearrange into a three dimensional structure.…”
Section: Effect Of Curing Time and Ka/ks On The Ucs Of The Geoploymersmentioning
confidence: 99%
“…However, elevated temperature curing was required to accelerate the hardening of the specimens. Ren et al also showed that aluminium sludge could be effective as a secondary source of Al 2 O 3 in an alkali‐activated blend with copper mine tailings, to decrease the overall Si/Al molar ratio and improve the performance of the resulting binders.…”
Section: Wastes From the Mining And Mineral Industriesmentioning
confidence: 79%